Steel surface defect detection and segmentation using deep neural networks - Sara Ashrafi; Sobhan Teymouri; Sepideh Etaati; Javad Khoramdel; Yasamin Borhani; Esmaeil Najafi (Results in Engineering)
Defect detection is a crucial task in the manufacturing industry, particularly in steel surface inspection. While manual recognition is one of the most reliable techniques, recent advances in computer vision and machine learning have led to the development of automatic defect detection techniques. This paper proposes several deep-learning-based computer vision techniques, including semantic segmentation and object detection models, to detect surface defects on steel sheets. The U-Net, FCN-8, and FPN models are implemented for segmentation, while the YOLOv4 model is used for object detection. Moreover, a combined segmentation and object detection structure, referred to as two-stage defect detection, is developed to enhance the accuracy of detecting small defects. Based on the obtained results, the U-Net model with pre-trained backbones achieves a Dice Similarity Coefficient of 72%, outperforming existing methods. The object detection model with a resolution of 640 reaches the mean average precision of 49.32% and 35.06% for binary class and multi-class detection, respectively. Furthermore, the proposed two-stage defect detection structure achieves a Dice Similarity Coefficient of 84%. In summary, the results validate the efficient performance of the studied techniques for accurate defect detection on steel surfaces.